Difficulties of the tactile sensory system sensory integration of children with autism - Salkić, Naim; Ahmetović, Zulfo; Velić, Safet; Krnojelac, Lara (Technium Social Sciences Journal, 2022)
Sensory integration represents the organization of the senses for their use. It is a neuro-biological activity that allows the reception and processing of sensory information, which in arrive from the senses in huge quantities into the brain, at any time. The ability of the brain to successfully process tactile information allows the child to feel safe and develop a connection with those around it. An autistic child is not able to register many stimuli from their environment, so insufficient or poor sensory processing can contribute to the image of autism. Children with autism spectrum difficulties have specific difficulties in touch perception. The aim of the study was to examine the prevalence of sensory integration difficulties of the tactile sensory system of children with autism spectrum disorders, and to establish the statistical significance of differences in relation to children without developmental difficulties. The total sample of subjects (N=30) consisted of two subsamples. The first subsample of subjects (N=15) consisted of children with difficulties from the autism spectrum, and the second subsample of subjects (N=15) consisted of children without developmental difficulties. The measurement instrument was the „Questionnaire for testing tactile sensory sensitivity“ with 11 variables and the offered answers of possible sensory response was applied. The Mann-Whitney U test and the Wilcoxon W test at the level of statistical significance of p<0.05 were used to examine the statistical significance of the differences between the subsamples of the subjects. The results of the study showed that 86.67 % of children with autism have difficulties in sensory integration of the tactile sensory system. The hypersensitive type of sensory response has 26.67 %, and the hyposensitive sensory response 20 % of children with autism. 40.00 % of children with autism have a mixed type of tactile sensory. There is a statistically significant difference between children with autism and children without developmental difficulties on 4 variables.